Digital Archaeology: A Review of the Application of Information Technology in Archaeological Data Management and Analysis - Xu, Kezhen (Transactions on Environment, Energy and Earth Sciences, 2024)
This paper provides a comprehensive review of the current application of information technology in archaeological data management and analysis, discusses the progress and practical application of digital archaeology, and looks ahead to its future development directions and challenges. With the rapid development of information technology, archaeology has gradually introduced digital tools such as database management systems, geographic information systems (GIS), remote sensing technology, virtual reality (VR), and augmented reality (AR). These technologies not only improve the efficiency of data management but also offer entirely new methods for analysis and presentation in archaeological research. This paper evaluates the application of different digital tools in archaeology, analyzes their technical advantages and limitations, and proposes strategies to address issues related to technical complexity, data standardization, and interdisciplinary collaboration. The study aims to provide valuable references for archaeologists, technology developers, and cultural heritage conservation professionals, promoting the further development and application of digital archaeology to achieve the efficient preservation and dissemination of cultural heritage.